2004
DOI: 10.1373/clinchem.2004.031765
|View full text |Cite
|
Sign up to set email alerts
|

D-Dimer Testing for Deep Venous Thrombosis: A Metaanalysis

Abstract: Background: The use of D-dimer assays as a rule-out test for deep venous thrombosis (DVT) is controversial.To clarify this issue we performed a systematic review of the relevant literature. Methods: We identified eligible studies, using MED-LINE entries from February 1995 through October 2003, supplemented by a review of bibliographies of relevant articles. Studies reporting accuracy evaluations comparing D-dimer test results with lower extremity ultrasound or venography in symptomatic patients with suspected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
94
1
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 91 publications
1
94
1
3
Order By: Relevance
“…[14][15][16][17] Despite the widespread use of Ddimer measurement, clinicians are puzzled by the high variability in numerical results produced by the different methods now available. Indeed, one of the main problems of D-dimer assays is that it is not currently possible to standardize results from different assays, [18][19][20][21][22][23] making it difficult to extrapolate results from one setting to another.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Despite the widespread use of Ddimer measurement, clinicians are puzzled by the high variability in numerical results produced by the different methods now available. Indeed, one of the main problems of D-dimer assays is that it is not currently possible to standardize results from different assays, [18][19][20][21][22][23] making it difficult to extrapolate results from one setting to another.…”
Section: Discussionmentioning
confidence: 99%
“…More than 75% of the patients in whom deep vein thrombosis (DVT) 3 is suspected and who are referred for objective testing-commonly performed with legcompression ultrasonography-do not have DVT (1,2 ). D-dimer testing for DVT has been introduced to improve the diagnostic process and, in particular, to reduce the number of unnecessary referrals for leg-compression ultrasonography.…”
mentioning
confidence: 99%
“…Concentrations of D-dimer are increased in patients with DVT, but may also be increased in other conditions such as cancer, infections, pregnancy, and recent surgery. Hence, D-dimer tests are typically used as rule-out tests (3,4 ). Although D-dimer testing is readily available to many hospital physicians within their central laboratories, this is often not the case for primary care physicians.…”
mentioning
confidence: 99%
“…16 It has been well established that clinical signs and symptoms are unreliable in identifying a DVT. 1,4,5,7,13,14,17 The classic Homan's sign is commonly used; however, because of its high false-positive and false-negative rates, results are frequently misleading, 8,12 making this test of little benefit. In contrast, clinical prediction rules (CPRs), such as those described by Wells et al, [17][18][19][20][21] known as the Wells score, have proven much more reliable and clinically meaningful in the outpatient population.…”
Section: T T Discussionmentioning
confidence: 99%
“…1 However, a metaanalysis that included 23 diagnostic accuracy studies of the D-dimer test reported a wide range of sensitivity values (0.51-1.00), with more than 33% of the studies reporting sensitivity values less than 0.90. 8 Due to the very serious potential complications of misdiagnosing an existing DVT, a negative D-dimer must not be considered a definitive test, particularly if the pretest probability of a DVT is high or moderately high. In this case, it is important to realize that, had the D-dimer test been negative, a more definitive study, such as compression ultrasound, would have been requested due to the high pretest probability of DVT.…”
Section: Discussion Dmentioning
confidence: 99%